DETERMINAN PERINGKAT OBLIGASI PERUSAHAAN DI INDONESIA - Isti Fadah; Siti Imas Wanti Zainia; Novi Puspitasari (UNEJ e-Proceeding)
This research,  examines the influence of solvency ratio, profitability ratio, liquidity ratio bond rating of non-Financial Institutions listed at BEI (Indonesia Stock Exchange) from 2010-2013. The sample of the study consist 17 non-financial institution.. It Uses logistic regression for testing the hypothesis. The results show that only profitability ratio has significant effect on bond rating. The solvency ratio and liquidity ratio don’t have significan  effect on bond rating.